The impact of a cash transfer program on cognitive achievement: the Bono de Desarrollo Humano of Ecuador - Juan Ponce; Arjun S. Bedi (Institute for the Study of Labor (IZA), 2008)
Throughout Latin America, conditional cash transfer (CCT) programs play an important role in social policy. These programs aim to influence the accumulation of human capital, as well as reduce poverty. In terms of educational outcomes, a number of impact evaluation studies have shown that such programs have led to an increase in school enrollment, ensured regular school attendance and led to a reduction in child labor. Theoretically, such cash transfer programs may also be expected to exert a positive impact on students' test scores, but related empirical evidence is scarce. Accordingly, this paper evaluates the impact of a cash transfer program, the Bono de Desarrollo Humano of Ecuador, on students' cognitive achievements. The paper uses a regression discontinuity strategy to identify the impact of the program on second grade cognitive achievement. Regardless of the specification and the sample used, we find that there is no impact of the program on test scores, suggesting that attempts at building human capital, as measured by cognitive achievement, require additional and alternative interventions.
urn:nbn:de:101:1-20080828301
Keywords: I38; 330; Cash transfers; test scores; regression discontinuity; Sozialhilfe; Konditionen; Kinder; Bildungsverhalten; Wirkungsanalyse; Bildungsniveau; Kognition; Ecuador